The Rising of “Alblish” (Albanian + English)—Data Collection and Analysis of Anglicisms in the Albanian Language - Kapo, Irena (Frontiers in Communication, 2022)
This paper investigates the impact of English on the Albanian language, a language contact phenomenon hitherto largely unexamined by Albanian and non-Albanian linguists alike. This contact mainly started as an indirect one at the beginning of the 20th century, primarily via translations, the establishment of several educational institutions with the support of American and British associations, Albanian immigration into English-speaking countries, etc. Several newspapers introduced a considerable number of Anglicisms into Albanian during the first half of the 20th century, a good quantity of which ‘survived’ even during the communist years of isolation. Those Anglicisms which made their way into the Albanian language until the 1990s and which have established themselves in the Albanian of today are mainly from the domains of culture and sports. The fall of the communist regime exposed the Albanian language to external linguistic and social factors, bringing about a flood of Anglicisms in different lexical fields other than culture and sport, such as business, information technology, politics, medicine, etc. The current database of Anglicisms in Albanian used for the purpose of this Brief Research Article was collected in the framework of the GLAD (Global Anglicism Database Network) project, http://gladnetwork.org.